Nature of functional links in valuation networks differentiates impulsive behaviors between abstinent heroin-dependent subjects and nondrug-using subjects - Zhai, Tianye; Shao, Yongcong; Chen, Gang; Ye, Enmao; Ma, Lin; Wang, Lubin; Lei, Yu; Chen, Guangyu; Li, Wenjun; Zou, Feng; Jin, Xiao; Li, Shi-Jiang; et al. (NeuroImage (Orlando, Fla.), 2015)
Advanced neuroimaging studies have identified brain correlates of pathological impulsivity in a variety of neuropsychiatric disorders. However, whether and how these spatially separate and functionally integrated neural correlates collectively contribute to aberrant impulsive behaviors remains unclear. Building on recent progress in neuroeconomics toward determining a biological account of human behaviors, we employed resting-state functional MRI to characterize the nature of the links between these neural correlates and to investigate their impact on impulsivity. We demonstrated that through functional connectivity with the ventral medial prefrontal cortex, the δ-network (regions of the executive control system, such as the dorsolateral prefrontal cortex) and the β-network (regions of the reward system involved in the mesocorticolimbic pathway), jointly influence impulsivity measured by the Barratt impulsiveness scale scores. In control nondrug-using subjects, the functional link between the β- and δ-networks is balanced, and the δ-network competitively controls impulsivity. However, in abstinent heroin-dependent subjects, the link is imbalanced, with stronger β-network connectivity and weaker δ-network connectivity. The imbalanced link is associated with impulsivity, indicating that the β- and δ-networks may mutually reinforce each other in abstinent heroin-dependent subjects. These findings of an aberrant link between the β- and δ-networks in abstinent heroin-dependent subjects may shed light on the mechanism of aberrant behaviors of drug addiction and may serve as an endophenotype to mark individual subjects' self-control capacity. •We characterized the nature of functional links between valuation networks.•With the functional links to vmPFC, δ and β networks were found jointly influence the impulsivity.•The δ and β networks were balanced and competitively control impulsivity in CN group.•The δ and β networks were imbalanced and mutually reinforce impulsivity in HD group.•This altered δ–β relationship could serve as an endophenotype of aberrant behaviors.